State Legislative Earmarks: Counterparts of Congressional Earmarks?. (June 2015) - Wu, Yonghong; Williams, Dan
Using data of "member items" in New York State during 2007–2010, we investigate how political factors such as majority party affiliation, tenure of service, and legislative leadership affect the distribution of state earmarked funds. The statistical results suggest that majority party affiliation and tenure of service have significant effects on the total earmarked funding state legislators may receive each year. Senate leaders or members of the Assembly Ways and Means Committee can also secure additional earmarks to fund their community projects. This research fills the gap in literature on subnational earmarking.